The Role of Digitalization in Enhancing Legal Competencies of Sharia Economic Law Graduates: A Case Study of graduate users in South Kalimantan - Amelia Rahmaniah; Fuad Luthfi; Muhammad Haris (Syariah: Jurnal Hukum dan Pemikiran, 2023)
Abstract: This study aims to identify the needs of graduate users and also show the strategies adopted by the Sharia Economic Law Study Program at Antasari State Islamic University in designing innovative curriculum and learning processes to produce graduate standards that are under the needs and desires of users. The informants in this study were graduate users who were selected based on the criteria of having alumni working in both government and non-government (private) agencies in South Kalimantan. The results showed that the needs of graduate users of the Sharia Economic Law Study Program include integrity, professionalism, foreign language skills, information technology skills, communication skills, cooperation skills, and self-development skills. In addition, the integration of technology in the learning process has also increased efficiency and effectiveness in transferring legal knowledge and skills to students.Keywords: Legal Competence, Sharia Economic Law, Graduate Users, Science Integration. Abstrak: Penelitian ini bertujuan untuk mengidentifikasi kebutuhan pengguna lulusan dan juga menunjukkan strategi yang ditempuh oleh Program Studi  Hukum Ekonomi Syariah Universitas Islam Negeri Antasari dalam merancang kurikulum dan proses pembelajaran inovatif untuk menghasilkan standar lulusan yang sesuai dengan kebutuhan dan keinginan para pengguna. Informan dalam penelitian ini adalah para pengguna lulusan yang dipilih berdasarkan kriteria adanya alumni yang bekerja baik di instansi pemerintah dan non pemerintah (swasta) yang ada di Kalimantan Selatan. Hasil penelitian menunjukkan bahwa kebutuhan pengguna lulusan terhadap Program Studi Hukum Ekonomi Syariah meliputi integritas, profesionalisme, kemampuan bahasa asing, kemampuan teknologi informasi, kemampuan komunikasi, kemampuan kerjasama, dan kemampuan pengembangan diri. Selain itu, integrasi teknologi dalam proses pembelajaran juga telah meningkatkan efisiensi dan efektivitas dalam mentransfer pengetahuan dan keterampilan hukum kepada mahasiswa.Kata Kunci: Kompetensi Hukum, Hukum Ekonomi Syariah, Pengguna Lulusan, Integrasi Ilmu.